The Mitochondrial Unfolded Protein Response: A Hinge Between Healthy and Pathological Aging - Muñoz-Carvajal, Francisco; Sanhueza, Mario (Frontiers in Aging Neuroscience, 2020)
Aging is the time-dependent functional decline that increases the vulnerability to different forms of stress, constituting the major risk factor for the development of neurodegenerative diseases. Dysfunctional mitochondria significantly contribute to aging phenotypes, accumulating particularly in post-mitotic cells, including neurons. To cope with deleterious effects, mitochondria feature different mechanisms for quality control. One such mechanism is the mitochondrial unfolded protein response (UPR-MT), which corresponds to the transcriptional activation of mitochondrial chaperones, proteases and antioxidant enzymes to repair defective mitochondria. Transcription of target UPR-MT genes is epigenetically regulated by Histone 3-specific methylation. Age-dependency of this regulation could explain a differential UPR-MT activity in early developmental stages or aged organisms. At the same time, precise tuning of mitochondrial stress responses is crucial for maintaining neuronal homeostasis. However, compared to other mitochondrial and stress response programs, the role of UPR-MT in neurodegenerative disease is barely understood and studies in this topic are just emerging. In this review, we document the reported evidence characterizing the evolutionarily conserved regulation of the UPR-MT and summarize the recent advances in understanding the role of the pathway in neurodegenerative diseases and aging.